Mass spectrometry-based metabolomics in health and medical science: a systematic review - Zhang, Xi-wu; Li, Qiu-han; Xu, Zuo-di; Dou, Jin-jin (RSC advances, 2020)
Metabolomics is the study of the investigation of small molecules derived from cellular and organism metabolism, which reflects the outcomes of the complex network of biochemical reactions in living systems. As the most recent member of the omics family, there has been notable progress in metabolomics in the last decade, mainly driven by the improvement in mass spectrometry (MS). MS-based metabolomic strategies in modern health and medical science studies provide innovative tools for novel diagnostic and prognostic approaches, as well as an augmented role in drug development, nutrition science, toxicology, and forensic science. In the present review, we not only introduce the application of MS-based metabolomics in the above fields, but also discuss the MS analysis technologies commonly used in metabolomics and the application of metabolomics in precision medicine, and further explore the challenges and perspectives of metabolomics in the field of health and medical science, which are expected to make a little contribution to the better development of metabolomics. Metabolomics is the study of the investigation of small molecules derived from cellular and organism metabolism, which reflects the outcomes of the complex network of biochemical reactions in living systems.